Complete genome sequence of the potato pathogen Ralstonia solanacearum UY031. Issue 1 (December 2016) - Guarischi-Sousa, Rodrigo; Puigvert, Marina; Coll, Núria; Siri, María; Pianzzola, María; Valls, Marc; Setubal, João
Abstract Ralstonia solanacearum is the causative agent of bacterial wilt of potato.Ralstonia solanacearum strain UY031 belongs to the American phylotype IIB, sequevar 1, also classified as race 3 biovar 2. Here we report the completely sequenced genome of this strain, the first complete genome for phylotype IIB, sequevar 1, and the fourth for theR. solanacearum species complex. In addition to standard genome annotation, we have carried out a curated annotation of type III effector genes, an important pathogenicity-related class of genes for this organism. We identified 60 effector genes, and observed that this effector repertoire is distinct when compared to those from other phylotype IIB strains. Eleven of the effectors appear to be nonfunctional due to disruptive mutations. We also report a methylome analysis of this genome, the first for aR. solanacearum strain. This analysis helped us note the presence of a toxin gene within a region of probable phage origin, raising the hypothesis that this gene may play a role in this strain's virulence.